Authentic leadership and employee creativity: testing the multilevel mediation model. Issue 3 (2nd May 2017) - Xu, Bao-Da; Zhao, Shu-Kuan; Li, Ci-Rong; Lin, Chen-Ju
Abstract : Purpose: The purpose of this paper is to test a multilevel framework to further explicate how team leaders' authentic leadership is related to their followers' individual creativity. Design/methodology/approach: This study is based on a questionnaire survey/analysis of analyses of multisource and lagged data from 63 team leaders and 428 followers in Taiwan. Findings: The findings demonstrated that leader-member exchange (LMX) and team psychological safe climate mediated the positive relationship of authentic leadership on followers thriving at work. Furthermore, employee thriving at work sequentially mediated the positive relationship between authentic leadership and employee creativity. The author also found that indirect relationship of LMX with employee creativity through thriving at work was stronger when authentic leadership was higher. Originality/value: The authors contribute to the existing understanding that authentic leadership relates to individual creativity through three multilevel mechanisms: leaders modeling their authenticity to develop and maintain their dyad-level exchange relationships with their followers (LMX), motivating the team, captured by team-level psychological safe climate and its members, reflected by employee-level thriving at work, and facilitating the relationship between LMX and employee thriving at work.